Kebiasaan Job Hopping Pada Pekerja Generasi Milenial - Ramadhani, Faisal; Komalasari, Shanty; Musfichin, Musfichin (Jurnal Al-Husna, 2023)
Job hopping is defined as someone who wants or tends to change jobs voluntarily in a span of less than two years. One of the dominant groups currently occupying employment is the millennial generation, this generation has a low commitment, which makes them just because they are under a little pressure, they can easily make decisions to change jobs, one of the phenomena that occurs among millennials in this era. now are workers who have the behavior of moving from one place of work to another after being accepted from where he works this generation has a habit that is different from the previous generation. This study aims to identify the factors that influence job hopping habits in millennial generation workers and seek an understanding of job hopping habits in millennial generation workers. The type of research that the researcher did was qualitative with the type of grounded theory. The subjects used were three people with the criteria of being born in 1981-2000, changing jobs based on their personal decisions and desires not due to various reasons of compulsion such as termination of employment (PHK). Methods of data collection using semi-structured interviews, observation and documentation. The results of this study were job hopping habits in millennial generation workers, MA subjects changed jobs five times, MT subjects changed jobs four times and SN subjects four times, all subjects stayed in one job for less than two years. Factors that influence job hopping habits in millennial generation workers are income, workplace location, work environment, boss at work, seeking experience and pressure at work. Keywords: Job Hopping; Millennial Generation; Worker